Virtual care beyond COVID-19: Patient and physician perspectives. Issue 28 (1st October 2022) - Abdelmutti, Nazek; Berlin, Alejandro; Macedo, Alyssa; Bender, Jackie; Liu, Zhihui (Amy); Papadakos, Janet; Lovas, Mike; Melwani, Sheena; Elliott, Mary; Moody, Lesley; Ashfaq, Iqra; Powis, Melanie Lynn; et al.
Abstract : 389 Background: The COVID-19 pandemic catalyzed rapid implementation of virtual care (VC), resulting in new opportunities to integrate technology and a need to evaluate patient and provider experiences. To inform sustainment beyond COVID-19, we evaluated perceptions of VC at a comprehensive cancer centre in Toronto, Canada. Methods: Physicians who provided VC during the pandemic, and patients with a valid email address on file and at least one visit with centre in the preceding 12 months were eligible to participate. Survey invitations were disseminated between May and July 2021 via email using a modified Dillman approach. The survey examined the implementation outcomes of acceptability, adoption, and appropriateness. Unadjusted associations between patient demographic variables and preference for in-person visits were evaluated using univariate logistic regression models. Results: 41% (100/246) of physicians and 15% (2, 343/15, 169) of patients completed the survey. The majority of patients were Caucasian (77%), college or university educated (78%), had solid malignancies (73%), and were in the follow-up phase (47%); 50% were male. The median age was 66 (IQR: 58-74). A greater proportion of patients expressed satisfaction with VC than providers (81% and 53%). Conversely, a greater proportion of providers felt that care delivered virtually was worse than care delivered in-person (45% vs 26%). Interestingly, many patients (69%) and physicians (40%) reported feeling they could maintain a good relationship through VC while at the same time reporting concerns that VC would detract from the human interaction they value as part of care (patients: 60%; providers: 82%). Patients expressed relatively equal preference for phone vs video visits (40% vs 31%), but indicated concerns about wait times for VC visits. The majority of physicians (37%) estimated that 10-29% of their practice would remain virtual post-COVID, however physicians expressed concerns with increased workload (72%), decreased efficiency (40%), and increased worry about missing relevant clinical information (61%). The majority of patients and physicians reported that VC was not appropriate for first consultations and discussions of prognosis, and most appropriate for long-term follow-up. Being born outside of Canada, primary language other than English, lower income, lower functional health literacy, and greater physical mobility were associated with preferring in-person over VC visits. Conclusions: Patients and physicians were satisfied with VC but expressed concerns with the impacts on care quality and experience and highlighted the need for guidelines on appropriate use. Providers expressed greater concerns with VC than patients. More research is needed to formally evaluate the impact of VC on quality performance and clinical outcomes as well as investigate the patient, disease and system factors that are associated with effective virtual cancer care.